PENGARUH SERVICE QUALITY DALAM MENINGKATKAN KEPUASAN PADA PASIEN PUSKESMAS PADANG PASIR (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2019)
The purpose of this study was to see influence the effect of service quality consisting of tangible, empathy, responsiveness, reliability and assurance of patient satisfaction at the Padang Pasir Public health. This type of research is associative, this research using multiple regression analysis. The population in this study were all patients who used services at the Padang Pasir Public Health. The sample in this study amounted to 30 people who were taken using accidental sampling technique. The results showed that all service quality variables had a positive and significant effect on patient satisfaction at the Padang Pasir Public health.